Sweet Syndrome - A Review of Pathogenesis, Clinical Features, Diagnosis and Treatment - Agnieszka Błaszczyk; Sara Trojan; Urszula Fussek-Styga; Jakub Kwieciński; Sławomir Miszuda; Bartosz Basiaga; Krzysztof Bednarz; Agata Szwedkowicz; Marek Leśniak; Jakub Heluszka (Kazimierz Wielki University, 2023)
Sweet syndrome is a rare, inflammatory, non-infectious skin disorder characterized by an acute onset of skin leasions such as painful, erythematous plaques, nodules and papules, most frequently located on the upper extremities, trunk, neck and face. Generally, dermatological symptoms are accompanied by fever, headaches, arthralgia and leukocytosis. The syndrome belongs to the group of febrile neutrophilic dermatoses. Skin biopsy reveals a diffuse, neutrophilic infiltrate in the upper dermis. Sweet syndrome presents in three clinical subtypes: classical, malignancy-associated and drug-induced. The etiology of this disease still remains unclear, but it seems that can be associated with dysfunction of the immune system, genetic predispostion and neoplastic process. Sweet syndrome has been reported in relation to pregnancy, drug administration, vaccinaton and infection of the respiratory or digestive system. Systemic glucocorticosteroids still remain the first line treatment for most patients, nevertheless new therapeutic options against reccurent Sweet syndrome have been investigated.